ВЛИЯНИЕ ГЛЮКОЗЫ И ИНСУЛИНА НА АКТИВНОСТЬ NOX В КРОВИ БОЛЬНЫХ САХАРНЫМ ДИАБЕТОМ И РЕГУЛЯЦИЯ ЕЁ ПОСРЕДСТВОМ ЭМБРИОНАЛЬНОГО ПРОТИВООПУХОЛЕВОГО МОДУЛЯТОРА - Е. А. Агаджанова (SINAPS LLC, 2014)
In 24 patients with type 1 and 2 diabetes and 12 donors was shown that in diabetes the Nox releasing of membrane of blood formations is significantly enhanced. This phenomenon is more pronounced in type 2 diabetes, indicating a greater violation of the stability of erythrocyte membranes (EM) and serum exosomes (SE). Under the influence of exogenous glucose releasing of Nox is further enhanced to a greater extent, in particular from SE. Influenced insulin in vitro releasing Nox in EM and SE also increases in. Based on a number of data , it has been suggested the possible role of Nox as the insulin receptor. It is shown that in the serum membranous structures of patients with type 1 diabetes treated with insulin, as well as the addition of insulin into the blood of patients with type 2 diabetes the releasing of Nox was significantly higher than in healthy donors. In the presence of Embryonal antitumor modulator of Mkrtchyan (EATM) the releasing of Nox is significantly inhibited, especially in patients with type 2 diabetes. Suppression of the Nox isoforms releasing of EM and SE in patients with diabetes under the influence EATM can be considered as a possible mechanism of its membrane stabilizing effect in vivo.